2022
DOI: 10.1038/s41467-022-28289-6
|View full text |Cite
|
Sign up to set email alerts
|

Exogenic origin for the volatiles sampled by the Lunar CRater Observation and Sensing Satellite impact

Abstract: Returning humans to the Moon presents an unprecedented opportunity to determine the origin of volatiles stored in the permanently shaded regions (PSRs), which trace the history of lunar volcanic activity, solar wind surface chemistry, and volatile delivery to the Earth and Moon through impacts of comets, asteroids, and micrometeoroids. So far, the source of the volatiles sampled by the Lunar Crater Observation and Sensing Satellite (LCROSS) plume has remained undetermined. We show here that the source could no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…However, here we show that not all of the ice deposits may represent pure ice, potentially changing the timing of the cometary impact. In fact, cometary impacts have been shown to be the likely source of lunar water at the near surface (Mandt et al 2022) and so the state of the Mercurian deposits may help shed light on the timing of the impact. Additionally, we found that the observed gradational pattern in SC radar backscatter occurs in both large and small craters.…”
Section: Discussionmentioning
confidence: 99%
“…However, here we show that not all of the ice deposits may represent pure ice, potentially changing the timing of the cometary impact. In fact, cometary impacts have been shown to be the likely source of lunar water at the near surface (Mandt et al 2022) and so the state of the Mercurian deposits may help shed light on the timing of the impact. Additionally, we found that the observed gradational pattern in SC radar backscatter occurs in both large and small craters.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the existence of water produced by impacts from meteoroids in known streams was discovered by LADEE, though it can be interpreted as preexisting lunar water liberated by the impacts rather than exogenic delivery (Benna et al 2019). Analysis of the LCROSS plume indicates a cometary origin for the volatiles in the permanently shadowed region of Cabeus (Mandt et al 2022), where we also detect water with SOFIA. Further SOFIA observations covering a wider range of latitudes are being analyzed and will address latitude variations as well as localized emission in the 6 μm feature.…”
Section: Discussion Of the Potential Relation To The Source Of The Lu...mentioning
confidence: 62%
“…Second, volcanic activity‐driven water is supplied equally during the Imbrian. This contribution, however, is currently under debate (Aleinov et al., 2019; Mandt et al., 2022). Third, the water supply made by asteroids and comets is proportional to their impact fluxes and so determined by applying the Neukum chronology model (Neukum et al., 2001).…”
Section: Water Redistribution At Lunar South Polementioning
confidence: 99%